HIV-1 Gag targeting to the plasma membrane reorganizes sphingomyelin-rich and cholesterol-rich lipid domains - Nario Tomishige; Maaz Bin Nasim; Motohide Murate; Brigitte Pollet; Pascal Didier; Julien Godet; Ludovic Richert; Yasushi Sako; Yves Mély; Toshihide Kobayashi (Nature Communications, 2023)
Abstract Although the human immunodeficiency virus type 1 lipid envelope has been reported to be enriched with host cell sphingomyelin and cholesterol, the molecular mechanism of the enrichment is not well understood. Viral Gag protein plays a central role in virus budding. Here, we report the interaction between Gag and host cell lipids using different quantitative and super-resolution microscopy techniques in combination with specific probes that bind endogenous sphingomyelin and cholesterol. Our results indicate that Gag in the inner leaflet of the plasma membrane colocalizes with the outer leaflet sphingomyelin-rich domains and cholesterol-rich domains, enlarges sphingomyelin-rich domains, and strongly restricts the mobility of sphingomyelin-rich domains. Moreover, Gag multimerization induces sphingomyelin-rich and cholesterol-rich lipid domains to be in close proximity in a curvature-dependent manner. Our study suggests that Gag binds, coalesces, and reorganizes pre-existing lipid domains during assembly.